Characteristics of patients with brain metastases from human epidermal growth factor receptor 2-positive breast cancer: subanalysis of Brain Metastases in Breast Cancer Registry - Laakmann, E.; Witzel, I.; Neunhoeffer, T.; Park-Simon, T-W; Weide, R.; Riecke, K.; Polasik, A.; Schmidt, M.; Puppe, J.; Mundhenke, Christoph; Lubbe, K.; Hesse, T.; et al. (ESMO Open, 2022)
Background: Up to 40% of patients with metastatic human epidermal growth factor receptor 2 (HER2)-positive breast cancer develop brain metastases (BMs). Understanding of clinical features of these patients with HER2-positive breast cancer and BMs is vital. Patients and methods: A total of 2948 patients from the Brain Metastases in Breast Cancer registry were available for this analysis, of whom 1311 had primary tumors with the HER2-positive subtype. Results: Patients with HER2-positive breast cancer and BMs were—when compared with HER2-negative patients—slightly younger at the time of breast cancer and BM diagnosis, had a higher pathologic complete response rate after neoadjuvant chemotherapy and a higher tumor grade. Furthermore, extracranial metastases at the time of BM diagnosis were less common in HER2-positive patients, when compared with HER2-negative patients. HER2-positive patients had more often BMs in the posterior fossa, but less commonly leptomeningeal metastases. The median overall survival (OS) in all HER2-positive patients was 13.2 months (95% confidence interval 11.4-14.4). The following factors were associated with shorter OS (multivariate analysis): older age at BM diagnosis [≥60 versus <60 years: hazard ratio (HR) 1.63, P < 0.001], lower Eastern Cooperative Oncology Group status (2-4 versus 0-1: HR 1.59, P < 0.001), higher number of BMs (2-3 versus 1: HR 1.30, P = 0.082; ≥4 versus 1: HR 1.51, P = 0.004; global P = 0.015), BMs in the fossa anterior (HR 1.71, P < 0.001), leptomeningeal metastases (HR 1.63, P = 0.012), symptomatic BMs at diagnosis (HR 1.35, P = 0.033) and extracranial metastases at diagnosis of BMs (HR 1.43, P = 0.020). The application of targeted therapy after the BM diagnosis (HR 0.62, P < 0.001) was associated with longer OS. HER2-positive/hormone receptor-positive patients showed longer OS than HER2-positive/hormone receptor-negative patients (median 14.3 versus 10.9 months; HR 0.86, P = 0.03), but no differences in progression-free survival were seen between both groups. Conclusions: We identified factors associated with the prognosis of HER2-positive patients with BMs. Further research is needed to understand the factors determining the longer survival of HER2-positive/hormone receptor-positive patients.
CRIS-Team Scopus Importer:2022-11-17
Keywords: brain metastases; breast cancer; HER2 positive; triple positive